Application of the complex variable function method in solving the floor heave problem of a coal mine entry - Yang, Jing-Hu; Song, Gao-Feng; Yang, Yi; Yang, Zeng-Qiang (Arabian journal of geosciences, 2018)
With the increase of mining depth in Chinese coal mines, the entry floor heave becomes one of the major engineering problems. This paper has studied the stress and displacement distribution around an entry in Buertai coal mine, China. The mechanism of floor heave is analyzed using the method of complex variable function. The influences of floor mechanical properties, longwall face advance, and mine water on the stability of the floor are then identified. The results show that (1) the floor moves towards the center under the concentration of the tangential stress, resulting in floor heave; (2) the floor stability is mainly influenced by the mechanical properties of the floor and the confining stress from the surrounding rock; and (3) the unnoticeable movement of the floor may be enlarged by the mining activity (face advance) and mine water. The proposed theoretical model is validated by the numerical modeling and the in situ. Good agreements are found between the theoretical analysis and the numerical modeling results and the in situ. It is thus believed that the complex variable function method can be used for analyzing the floor heave problem. Based on the mechanism of floor heave, we divide the control techniques into two categories: creation of a stress-relief entry and floor reinforcement. The techniques were practiced at two Chinese coal mines with good ground control effects.